2016
DOI: 10.1007/s11250-016-1108-4
|View full text |Cite
|
Sign up to set email alerts
|

Total replacement of corn by mesquite pod meal considering nutritional value, performance, feeding behavior, nitrogen balance, and microbial protein synthesis of Holstein-Zebu crossbred dairy steers

Abstract: The objective of the present study to assess the effects of mesquite pod addition replacing corn (0, 250, 500, 750, and 1000 g/kg in the dry matter basis) on nutrient intake, animal performance, feeding behavior, nutrient digestibility, nitrogen balance, and microbial protein synthesis. Twenty-five Holstein-Zebu crossbred dairy steers at 219 ± 22 kg initial body weight and 18 months of age were used. The experiment lasted 84 days, divided into three periods of 28 days. A completely randomized design was used, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The mesquite silage presented the greatest value for NDF of all documented figures. This is not surprising, however, given that most investigations have selected individual plant parts, such as pods [ 10 , 11 , 12 , 14 , 31 , 32 ], leaves [ 7 , 8 , 29 ], or seeds [ 14 , 28 , 33 , 34 ]. Pulp, the most similar product to the whole-plant biomass used in the current study, was only evaluated in one previous manuscript [ 9 ], and this experiment did not evaluate the commonly found P. juliflora .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mesquite silage presented the greatest value for NDF of all documented figures. This is not surprising, however, given that most investigations have selected individual plant parts, such as pods [ 10 , 11 , 12 , 14 , 31 , 32 ], leaves [ 7 , 8 , 29 ], or seeds [ 14 , 28 , 33 , 34 ]. Pulp, the most similar product to the whole-plant biomass used in the current study, was only evaluated in one previous manuscript [ 9 ], and this experiment did not evaluate the commonly found P. juliflora .…”
Section: Discussionmentioning
confidence: 99%
“…Dutta et al [ 7 ] found that leaves of P. cineraria (L.) Druce improved the digestibility coefficients of all measures of nutritive value when supplemented to a rice straw diet in goats, while Bhatta et al [ 8 ] found mixed results of P. cineraria leaf supplementation of lambs and kids. Much of the interest in feeding mesquite species to livestock has revolved around the use of pods [ 9 , 10 , 11 , 12 ] or seeds [ 13 ] as a protein source as mesquite belongs to the Fabaceae family [ 5 ]. Few, though, have investigated the total biomass of mesquite.…”
Section: Introductionmentioning
confidence: 99%
“…The primary benefits were the provision of charcoal, pods for fodder and fuel wood as sources of cheap energy in a remote area. These products directly contributed as income sources (charcoal and fuel wood) and as replacements for expensive animal fodders (pods and leaves) as others have indicated [29,31,52,53]. The results provided the estimated annual income for the household from P. juliflora (JOD 2167) considering the scenario in which the current forestry law is modified to allow for legal use.…”
Section: Discussionmentioning
confidence: 99%
“…The replacement of corn with P. juliflora pod meal in cattle feed did not affect nutrient intake, total weight gain, nutrient digestibility, or nitrogen intake. The pod meal of P. juliflora also provided a better performance of the ruminal microbiota 12 . Khobondo et al 26 .…”
Section: Use Of P Juliflora Pods and Seeds And Their Derivatives In F...mentioning
confidence: 97%
“…The fruits of P. juliflora are pods studied because they have a high nutritional value and have strong potential to be introduced into human consumption. They can also be included in manufacturing products in the food industry, 11 providing a viable and sustainable alternative 12 . The pods contain high protein and carbohydrates and are rich in fiber, lipids, and minerals 13 .…”
Section: Introductionmentioning
confidence: 99%